(untitled) (Homoeopathy for All, 2026)
The following case report is alopecia areata in 24 years old male who was treated successfully with individualised homoeopathic medicine within 6 months of treatment. Syphilinum was prescribed as a constitutional remedy on the basis of totality of symptoms and after the repertorisation. Homoeopathic medicines have wonderful results in such type of cases, where the modern medicines have very less effective treatment.